ADAPT system is a dramatic advance in computer-assisted surgery for femoral trochanteric fractures - Murakami Tomotoshi (EDP Sciences, 2021)
Introduction: In recent years, computer-assisted surgery has made it possible to undergo surgery with a high degree of precision. This study aimed to investigate the usefulness of computer-assisted surgery for femoral trochanteric fractures using the ADAPT (ADAptive Positioning Technology) system. Methods: A total of forty patients with femoral trochanteric fracture underwent intramedullary nailing for fracture fixation: in twenty patients, the ADAPT system (ADAPT group), and in the other twenty, it was not used (control group). The operative time, intraoperative fluoroscopy time, tip apex distance (TAD), and tip to head surface distance (TSD) were measured and compared between the two groups to assess the efficiency and accuracy of the surgery. Results: The operative time was significantly shorter (P < 0.05), intraoperative fluoroscopy time was significantly reduced (P < 0.01), and implant placement was significantly better in the ADAPT group (P < 0.01). Conclusion: Navigation systems have been developed to improve the efficiency of surgery. The ADAPT system was considered a very useful device for intramedullary nailing of femoral trochanteric fractures, as it reduced the intraoperative fluoroscopy time and improved the accuracy of implant placement, also reducing the operative time.